2022
DOI: 10.31083/j.jin2101042
|View full text |Cite
|
Sign up to set email alerts
|

Citrus limon L. (lemon) seed extract shows neuro-modulatory activity in an in vivo thiopental-sodium sleep model by reducing the sleep onset and enhancing the sleep duration

Abstract: Citrus limon L. is an ingenious alternative medication and has a broad scope in managing several health conditions as part of natural remedies. Recently, medicinal plants have witnessed incredible consideration worldwide in the field of neuroscience for remedial intervention. The present work has investigated the phytochemical compounds and neuropharmacological potential of the seed extract of Citrus limon as a step to partially validate its formulations as nutraceuticals using an in vivo model. Diverse phytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 64 publications
1
45
0
Order By: Relevance
“…A similar research from our group has previously been published by the authors Md. Mominur Rahman et al 2022 ( https://doi.org/10.31083/j.jin2101042 ), mentioned as reference number [ 58 ].…”
Section: Disclosurementioning
confidence: 70%
“…A similar research from our group has previously been published by the authors Md. Mominur Rahman et al 2022 ( https://doi.org/10.31083/j.jin2101042 ), mentioned as reference number [ 58 ].…”
Section: Disclosurementioning
confidence: 70%
“…In summary, our findings showed that EPS exhibits potent activities and should be considered a good option and an additional source of natural compounds for the treatment of hepatic fibrosis and hepatic injury. EPS is a promising drug candidate [ 26 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DSPN is a major contributor to neuropathic ulcers and infection, which can cause lower limb amputation [ 4 ]. There has been evidence that chronic systemic inflammation contributes to noncommunicable diseases, including cancer, cardiovascular disease, depression, and diabetes [ 5 , 6 ]. In fact, inflammation, oxidative stress, induced by chronic hyperglycemia, and mitochondrial dysfunction are the three most important risk factors in the pathogenesis of DSPN [ 7 ].…”
Section: Introductionmentioning
confidence: 99%